PENERAPAN MODEL DISCOVERY LEARNING PADA PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM BERDASARKAN JENIS KELAMIN SISWA - Murharyana; Al Ayyubi, Ibnu Imam; Riyadi, Dede Ahmad; Zahra, Aulia; Nugraha, Mohamad Fajar (Fakultas Agama Islam, Universitas Mathla'ul Anwar, 2024)
This research aims to see the differences in the Discovery Learning learning model in the History of Islamic Culture subject carried out in three schools by classifying student learning outcomes based on gender. This research was carried out at SMPN 2 Parongpong, SMP Unggulan Al Amin, and SMP Roudlotul Ulum using a quantitative research approach with a sample of 35 students at SMPN 2 Parongpong, 36 students at SMP Unggulan Al Amin, and 33 students at SMP Roudlotul Ulum for a total of 104 students. This research instrument uses a test with testing requirements for data analysis used consisting of a normality test and a homogeneity test using Shapiro-Wilk with the help of SPSS version 26 software. In this study it can be concluded that the learning outcomes in the History of Islamic Culture material using the Discovery Learning learning model at SMPN 2 Parongpong, Al Amin Unggulan Middle School, and Roudlotul Ulum Middle School, there are significant differences in the students' school origins but there are no differences based on gender and interactions that occur between school origins and students' gender. So that for further research, learning can be carried out on Islamic Cultural History material which is reviewed based on student learning outcomes based on school origin and cognitive stage using Analysis of Variance testing to see the differences and interactions that occur using the Discovery Learning model.